HUBUNGAN MUTU PELAYANAN DENGAN KEPUASAN PASIEN RAWAT JALAN DI RSUD PETALA BUMI PROVINSI RIAU : Hubungan Mutu Pelayanan Dengan Kepuasan Pasien - Firda Resty; Yesica Devis (STIKes Hang Tuah Pekanbaru, 2019)
Improving service quality is a top priority in a hospital management. Quality health services could be appeared from five dimensions, namely reliability, responsiveness, assurance, empathy, and tangibles. Excellent patients’ satisfaction will be obtained if health services applied were in better quality. This research aim was to find out the correlation between service quality with patients’ satisfaction in outpatient unit of Petala Bumi General Regional Hospital of Riau Province. This was a quantitative study with cross sectional design. Sample were 96 patients which taken by accidental sampling. Data analyzed was bivariate with used Chi Square Test. The result obtained there were correlation reliability ( P value = 0,021, value of OR 3,000), responsiveness ( P value = 0,000, value of OR 5,432), assurance (P value = 0,018, value of OR 3,096), emphaty (P value = 0,004, value of OR 3,850), tangible ( P value = 0,010, value of OR 3,392) with patients’ satisfaction in outpatient unit of Petala Bumi GRH of Riau Province. It could be concluded that there was a relationship between service quality and patients’ satisfaction at the outpatient unit at Petala Bumi GRH of Riau Province. This result suggests to the Petala Bumi GRH on Riau Province to create a strategy and efforts to improve the quality of health services in order to patients’ satisfaction cloud be increased continually.